The Effect of Mergers on Variety in Grocery Retailing - Elena Argentesi; Paolo Buccirossi; Roberto Cervone; Tomaso Duso; Alessia Marrazzo (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We study the effect of a merger between two Dutch supermarket chains to assess its effect on the depth as well as composition of assortment. We adopt a difference-in-differences strategy that exploits local variation in the merger's effects, controlling for selection on observables through a matching procedure when defining our control group. We show that the merger led the merging parties to reposition their assortment to avoid cannibalization in the areas where they directly competed before the merger. While the low-variety target's stores reduced the depth of their assortment when in direct competition with the acquirer, the latter increased their assortment. This suggests that variety is a strategic variable in retail chains' response to changes in local competition.
Keywords: L10; L41; L66; L81; D22; K21; C23; 330; variety; assortment; mergers; ex-post evaluation; retail sector; supermarkets; grocery